Genotoxic effects of chlorinated disinfection by-products of 1,3-diphenylguanidine (DPG): cell-based in-vitro testing and formation potential during water disinfection - Marques Dos Santos, Mauricius (2022)
1,3-diphenylguanidine (DPG) is a commonly used rubber and polymer additive, that has been found to be one of the main leachate products of tire wear particles and from HDPE pipes. Its introduction to aquatic environments and potentially water supplies lead to further questions regarding the effects of disinfection by-products potentially formed. Using different bioassay approaches and NGS RNA-sequencing, we show that some of the chlorinated by-products of DPG exert significant toxicity. DPG and its chlorinated by-products also can alter cell bioenergetic processes, affecting cellular basal respiration rates and ATP production, moreover, DPG and its two chlorination products, 1,3-bis-(4-chlorophenyl)guanidine (CC04) and 1-(4-chlorophenyl)-3-(2,4-dichlorophenyl)guanidine (CC11), have an impact on mitochondrial proton leak, which is an indicator of mitochondria damage. Evidence of genotoxic effects in the form of DNA double strand breaks (DSBs) was suggested by RNA-sequencing results and further validated by an increased expression of genes associated with DNA damage response (DDR), specifically the canonical non-homologous end joining (c-NHEJ) pathway, as determined by qPCR analysis of different pathway specific genes (XRCC6, PRKDC, LIG4 and XRCC4). Immunofluorescence analysis of phosphorylated histone H2AX, another DSB biomarker, also confirmed the potential genotoxic effects observed for the chlorinated products. In addition, chlorination of DPG leads to the formation of different chlorinated products (CC04, CC05 and CC15), with analysed compounds representing up to 42% of formed products, monochloramine is not able to effectively react with DPG. These findings indicate that DPG reaction with free chlorine doses commonly applied during drinking water treatment or in water distribution networks (0.2-0.5 mg/L) can lead to the formation of toxic and genotoxic chlorinated products.